Objective measurement of stiffness in knee osteoarthritis. - Burks K; Keegan K (Orthopaedic Nursing)
PURPOSE: The purpose of this study was to evaluate an objective measure of knee joint stiffness in older adults with and without knee osteoarthritis.DESIGN: Methodological study of the modified pendulum test. SAMPLE: A convenience sample of community-dwelling older adults (n=41).METHODS: Knee angle oscillation data were collected with a VICON motion analysis system and were used to calculate stiffness and damping coefficients and measures of joint stiffness. FINDINGS: Although some testing problems were encountered early in the study, useable data were obtained from 29 participants. Within-participant variability for calculated stiffness and damping coefficients was low (0.55% and 8.92%, respectively), whereas the between-participant variability was high for both the stiffness (99.45%) and damping (91.08%) coefficients. DISCUSSION: The modified pendulum test is a reliable method for evaluation of knee joint stiffness. This method can be used in collection of outcome data for future intervention studies addressing joint stiffness.